The Role of Knowledge Brokers in Education : Connecting the Dots Between Research and Practice - Malin, Joel; Brown, Chris (Routledge, 2019)
This ground-breaking book comprehensively addresses an area of major and sustained concern: how to improve the use of research evidence and enhance educators’